2017
DOI: 10.1038/ncomms15913
|View full text |Cite
|
Sign up to set email alerts
|

A practical and catalyst-free trifluoroethylation reaction of amines using trifluoroacetic acid

Abstract: Amines are a fundamentally important class of biologically active compounds and the ability to manipulate their physicochemical properties through the introduction of fluorine is of paramount importance in medicinal chemistry. Current synthesis methods for the construction of fluorinated amines rely on air and moisture sensitive reagents that require special handling or harsh reductants that limit functionality. Here we report practical, catalyst-free, reductive trifluoroethylation reactions of free amines exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 52 publications
(55 reference statements)
1
42
0
1
Order By: Relevance
“…These initial results were in agreement with related observations of Beller and co-workers. 33 We had previously observed that Brønsted acids react rapidly with phenylsilane to generate modied silanes with enhanced reducing properties 34 and, remarkably, the addition of 50 mol% of benzoic acid (entry 5) resulted in a substantial improvement in the yield to 65%. More signicantly, we found that the carboxylic acid could be changed to match that from which the secondary amide was derived (entry 6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These initial results were in agreement with related observations of Beller and co-workers. 33 We had previously observed that Brønsted acids react rapidly with phenylsilane to generate modied silanes with enhanced reducing properties 34 and, remarkably, the addition of 50 mol% of benzoic acid (entry 5) resulted in a substantial improvement in the yield to 65%. More signicantly, we found that the carboxylic acid could be changed to match that from which the secondary amide was derived (entry 6).…”
Section: Resultsmentioning
confidence: 99%
“…39 These signals we attribute to multiple silyl esters that are generated by a dehydrogenative silylation process which could be catalyzed by residual amine from the amidation step or, as the reaction progresses, by the amine product. 34 Having observed species that we believed to be silyl ester intermediates in the reduction phase of the reaction, we carried out a further experiment in which carboxylic acid 36 was treated with phenylsilane and catalytic N-methylmorpholine (Scheme 2B)conditions which will generate a mixture of silyl esters. 34 Gratifyingly, a similar 19 F NMR prole was observed ( 19 F d ¼ À103.9 to À105.2) along with some residual carboxylic acid.…”
Section: Mechanism: Role Of the Carboxylic Acidmentioning
confidence: 99%
“…The success in N ‐fluoroalkylation of amines with trifluoroacetic acid indicates that the present protocol might be a useful tool to introduce fluorine atoms to the β‐position of the N atom of complex secondary amines, which has shown beneficial effects for some drugs or drug candidates . To date, besides Denton's non‐catalytic trifluoroethylation of secondary aliphatic amines, only limited examples have been demonstrated previously for syntheses of N ‐trifluoroethylated aniline derivatives using relatively unstable trifluoroethylation reagents, such as trifluoroacetaldehyde and 2,2,2‐trifluorodiazoethane, or Pd‐catalyzed coupling of aryl halides and trifluroethylamine . The present protocol provides an air‐tolerant alternative approach under transition metal‐free conditions.…”
Section: Resultsmentioning
confidence: 99%
“…We recently showed that mild nucleophilic activation of relatively less reactive silicon‐hydride provides an alternative way to reduce CO 2 , in which the formation of metal‐hydride or boron‐hydride species can be avoided . This corresponds well with Denton's elegant catalyst‐free system in spite of its limited substrate scope, because it also doesn't proceed through the amide intermediates under mild reducing atmosphere . Therefore, we reasoned that suitable reducing capacity may enable the application of DNACA to a wide scope of amines.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, the methodologies of N‐(fluoroalkyl/fluoroacetyl)‐aniline synthesis include the following; N‐(fluoroalkyl‐/fluoroacetyl)‐aniline can be directly prepared by combination of aniline and trifluoroethylation/trifluoroacetyl reagents (scheme a). Alternatively, the fluoroalkyl/fluoroacetyl group can be introduced by Pd or Cu‐catalyzed coupling of aryl halides and fluoroalkylamine/trifluoroacetamide (scheme b) .…”
Section: Introductionmentioning
confidence: 99%